Metabolic syndrome in pre and post menopausal women of Bangladesh (Bangladesh Journal of Medical Science, 2018)
Objective: To assess the metabolic syndrome (MetS) status in pre and post menopausal women of Bangladesh.Materials and Methods: Secondary analysis from a cross-sectional study on 276 willing females from an urban and a rural area. The socio-epidemiologic factors were studied with anthropometric examination, blood pressure recording and fasting blood for analysis of triglyceride (TG), high density lipoprotein (HDL), fasting blood sugar (FBS) between pre and post menopausal women.Results and Discussion: Only 19.8% premenopausal women had MetS (95% CI=15.7%-24.7%) compared to that of 50% (95% CI=39.9%-60.1%) menopausal (p